PREVALENCE OF BARRETT'S ESOPHAGUS IN EASTERN TURKEY - Sahin, Abdurrahman; Artas, Gokhan (Carbone Editore, 2022)
Objective: To determine the prevalence of Barrett's Esophagus (BE) among patients undergoing esophagogastroduodenoscopy (EGD) in a tertiary care center in Eastern Turkey and to compare with the prevalences of other regions of Turkey. Methods: We retrospectively reviewed the endoscopy database and consecutive adult patients who underwent an EGD for any indication between January 2015 and December 2017 were included. Cases of endoscopically suspected and biopsied were evaluated and, biopsy proven BE were identified. Gastric and esophageal endoscopic and histopathological findings were evaluated. Results: A total of 8275 patients who underwent EGD, 241 patients (2.9%) had endoscopically suspected and biopsied for BE. Among them, 161 patients (1.9%) had biopsy proven BE. The mean age of the patients with BE was 48.0 +/- 16.7 years and only 74 patients (46%) were over 50 years. Of the 161 patients, 82 (51%) were women. Eight of them had long-segment BE (LSBE) (>3 cm) while 153 had short-segment Barrett's Esophagus (SSBE) (<= 3 cm). Only seven patients had low-grade dysplasia, and none had high-grade dysplasia. A total of 111 patients (61%) were positive for Helicobacter pylori. Gastric intestinal metaplasia was found in 22 (14%). Conclusions: The prevalence of BE in this study was found higher from other regions of Turkey. The reasons for these results should be further investigated.
Keywords: Barrett's esophagus; Gastroesophageal reflux disease; prevalence; Turkey